Impact of Digitalization on Elementary Students Cognition: The Brain Rot Phenomenon - Ruchiyat, Marina Gusnia; Putri, Salsa Shabrina; Hidayatika, Aliya; Putri, Dahlia; Mustadi, Ali (Juwara: Jurnal Wawasan dan Aksara, 2025)
This study aims to identify the impact of gadget use on the cognitive ability of elementary school students, focusing on the phenomenon of brain rot caused by excessive exposure to technology. The method used is a quantitative approach with survey and test design. A total of 10 students from SD N 7 Catur Tunggal became participants in this study. Data was collected through questionnaires regarding the duration of device use per day and cognitive tests that measured students' concentration, memory, and critical thinking. The results showed that students who spent more than 6 hours per day using gadgets had lower cognitive scores, indicating a decline in ability in all three cognitive aspects. In contrast, students who used their devices for less than 3 hours per day tended to show better cognitive test results, with a total score of 20-26. These findings showed a significant negative relationship between the duration of gadget use and students' cognitive ability (r = -0.55, p < 0.05), leading to the phenomenon of brain rot.